PEMBANGKIT LISTRIK PORTABEL BERBASIS PIEZOELEKTRIK UNTUK PENGISIAN ENERGI PADA HANDPHONE - Arifin, Zainal; Subito, Mery; Fauzi, Rizana; Alamsyah, Alamsyah; Indrajaya, Muhammad Aristo; Mustari, Aidynal (Foristek, 2025)
Electrical energy is a primary need in modern life that continues to increase along with the rapid development of technology and the use of portable electronic devices. Dependence on conventional power plants sourced from fossil fuels is considered unable to meet energy needs when outside the conventional electricity grid. Therefore, a more flexible and easy-to-produce renewable energy alternative is needed. One solution that can be offered is the use of piezoelectrics, which are capable of producing electrical energy only through mechanical pressure without relying on weather conditions such as solar power plants or wind power plants. This study aims to design and test a portable power generator based on piezoelectrics. The piezoelectric circuit is designed with a series-parallel configuration of 30 piezoelectric pieces, which are connected to rectifier diodes, elcos, storage batteries, and step- down modules for voltage adjustment to electronic devices. The test results show that the device can produce an output voltage of up to 32.47 VAC. Then, the highest DC voltage is 87.3 VDC. The voltage stored in Elco is 24.92 VDC, with the final output on the battery being 13.69 VDC and a current of 1 A within 2 minutes. Meanwhile, the time required to charge 1% on a mobile phone is 9 minutes, indicating the potential effectiveness of the device with further pressure increases.